(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The effect of soil moisture and tillage depth was studied based on some mechanical properties for type tillage machine (moldboard plow) and soil physical characteristics wene tested two soil moisture levels of 10-12%and 12-14% and three levels tillage depth of 14,16 and 18 cm. The experiments were conducted in a factorial experiment under a randomized complete block design with three replications. The results showed that the soil moisture 10-12 % was significantly better than the soil moisture 12-14% as while tillage depth at range 14cm was significantly superior to the other two levels 16 and 18 cm in all studied conditions. The results showed fuel consumption of 11.348 and 10.777 L.ha-1 , slippage percentage of 9.291 and 9.111 % power losses due to slippage of 2.689 and 2.414 kW, field efficiency of 68.358 and 68.967 %, drawbar power 12.226 and 12.001kw and specific resistance 9.045 and 8.553 N.cm-2 for soil moisture 10-12% and tillage depth 14 cm , respectively.